HAEMATOZOAN PREVALENCE OF DOMESTIC PIGEONS (Columba livia domestica) IN ERBIL PROVINCE, KURDISTAN REGION-IRAQ - Shwan Khursheed Rahman Basha (Polytechnic Journal)
Out of 70 domestic pigeons Columba livia domestica which collected from different localities in Erbil province, Kurdistan region- Iraq, and examined for blood parasite, only one species of blood protozoans (Haemoproteus colombae) was observed in 15 of them with overall prevalence 21.42%, according to the sex of infected pigeons statistically there were no significant differences between males (18.18%) and females (24.32%) infection with this blood parasite. No other haematozoa were detected.